Characterisation of the innate immune sensor MDA5 - Dias, A (2017)
Melanoma Differentiation-Associated gene 5 (MDA5) is a cytosolic RNA receptor. Its activation triggers the production of the antiviral cytokines type I and III Interferons (IFN). It is believed that MDA5 detects viral and/or cellular RNAs. The latter case may be relevant in the context of cancer treatment with DNA demethylating agents, and in autoinflammatory and autoimmune diseases. In all these settings, physiological MDA5 agonists have not been identified. To identify MDA5-stimulatory RNAs, we generated mouse monoclonal antibodies against human MDA5. We showed that some of these antibodies are specific and detect MDA5 protein by Western Blot, in immunofluorescence, and work in immunoprecipitation (IP). To identify MDA5's RNA ligands in living cells, we employed the UV-crosslinking and IP (iCLIP) technique. Interestingly, we found that MDA5 associated with RNAs regardless of virus infection. Sequencing and characterisation of these RNA species will be performed in the future. MDA5 overexpression led to IFN-I induction, which could be explained by MDA5 binding to cellular RNAs. Indeed, two bioassays developed here suggest that MDA5 can sense RNAs from uninfected human cells and tissues. In a second project, we demonstrated that Zika Virus (ZIKV) replication generated MDA5 and, RIG-I immunostimulatory RNAs. RIG-I-dependent IFN-I induction was sensitive to alkaline phosphatase treatment, in line with the requirement for 5'-ppp groups for RIG-I activation. Furthermore, by using a mini-screen of ZIKV proteins, we identified the non-structural protein 5 (NS5) as a potent inhibitor of the type I IFN signalling pathway. We show that this inhibitory mechanism is unrelated to: i) NS5's nuclear localisation, ii) mutations found in strains of the current outbreak, and iii) a conserved residue in the methyltransferase domain. In sum, we provide novel insights into the biology of MDA5, new reagents for the studies of MDA5, as well as data on the role of RNA sensors in detecting ZIKV infection and evasion of innate immunity by ZIKV.